미세수술을 이용한 두경부 결손부 재건에 있어서 피판 합병증 발견을 위한 혈청 C-reactive protein(CRP) 측정의 유용성 - Song Hyunsuk (The Graduate School, Ajou University, 2015)
Free microvascular head and neck reconstruction requires minimal complication and safety. However, clinical observation of the wound in head and neck area is very difficult because of its narrow and inaccessible anatomy. Serum C-reactive protein (CRP) level is commonly used as a marker of acute inflammatory response and quantitative test that shows predictable kinetics. Therefore, awareness of natural CRP trend of free microvascular head and neck reconstruction may help in the early diagnosis of postoperative complications. The goal of this study is to describe the time course of serum CRP level and prove the usefulness of CRP as a predictor of postoperative flap wound complication after performing free microvascular reconstruction in head and neck area. Between June 2009 and November 2012, we retrospectively analyzed the data of 25 patients who received free microvascular tissue transfer for head and neck reconstruction at Ajou University Hospital. The characteristics of patients and surgical information were analyzed. From the first day after surgery, serum CRP levels were daily measured for two weeks. The average CRP values were daily calculated for the normal group and the complicated group and compared between each groups. The amount of time taken to reach the peak CRP level and to reach half of the peak was compared. A Total of 25 patients were included in this study. The amount of time taken to ii reach the peak of the CRP level is significantly less in the normal group (2.88 days) than the complicated group (7 days) (p<0.001). Furthermore, the amount of time to reach half of the peak was significantly different between groups (7.19 days vs. 10.14 days, respectively, p<0.05). In the normal group (17/25), there were 14 cases which reached peak CRP level before postoperative day 4. However, in the complicated group (8/25), there was only 1 case which reached peak CRP level before postoperative day 4 (p< 0.05). The complication rate is 32.7 times higher when CRP value reaches peak on or after postoperative day 4 (95% Confidence interval, 30.26 - 35.14; p= 0.002). Patients in the complicated group showed significantly elevated CRP levels compared to those in the normal group at day 6 to 8 and day 12 (p< 0.05). In head and neck reconstructions, the high probability of flap wound complications are indicated through the result of having highest CRP values on or after postoperative day 4, slow normalization of serum CRP level and secondary rise in serial CRP values.
학위논문(박사)--아주대학교 일반대학원 :의학과,2015. 2
Keywords: serum C-reactive protein; free flap; head; neck; 혈청 c-반응 단백질; 유리 피판; 두부; 경부